2018
DOI: 10.21776/ub.afssaae.2018.001.02.5
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial marketing strategy on tempe sanan chips small and medium entreprises in Malang

Abstract: The development of national industry in Indonesia still faces a number of obstacles such as inadequate infrastructure condition, as well as an increase on subsidised fuel price increase, basic electricity rate and minimum wage. Small and medium scale (SME) food industry is one sector of creative industries with a high contribution to the Indonesian economic development. This study aims to get an overview related to agribased agri-sector SME and to identify internal and external factors to formulate appropriate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
4
0
Order By: Relevance
“…The higher improvement of the entrepreneurial marketing that is possessed by the business owner, the higher competitiveness industry will be in the future. This is supported by the result of research that capacity of entrepreneurial skill is the most important thing to be managed (Dwicahyo, 2012;Haryati, et. Al, 2018).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The higher improvement of the entrepreneurial marketing that is possessed by the business owner, the higher competitiveness industry will be in the future. This is supported by the result of research that capacity of entrepreneurial skill is the most important thing to be managed (Dwicahyo, 2012;Haryati, et. Al, 2018).…”
Section: Resultsmentioning
confidence: 78%
“…However, there are still threats, including incompatible government support such as LPG gas conversion and also threats from a very competitive market. Government support for the creation of fair trade and welfare of entrepreneurs is needed (Haryati, Surahman, Kurniawan, & Amalia, 2018) Entrepreneurial Marketing is a set of processes to create, communicate and provide value to customers and to manage customer relationships in a way that benefits the organization and stakeholders (Kraus, 2010) it is also an organizational function and, and it has the characteristics of innovativeness, risk-taking, proactiveness, and maybe done without controlled resources (Moral et al, 2010), According to Kotler & Armstrong (2012) in the early stages, when a company is small, flexible and willing to experience new things, a type of informal marketing is practiced and this will become Entrepreneurial Marketing. The emergence of the concept of entrepreneurial marketing is a response from several research results that show a mismatch between traditional marketing theory and marketing practices in small and medium-sized businesses, or SMEs (Ionita 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Entrepreneurship or entrepreneurial orientation has a relation to performance (Haryati et al, 2018;Haryati et al, 2019). Entrepreneurial Orientation (EO) is often mentioned as an antecedent of growth, competitive advantage, and superior performance, and prior empirical research has often shown a positive relationship between EO and performance appears to exist.…”
Section: Variable Of Research Can Be Seen Inmentioning
confidence: 99%
“…Research about marketing and entrepreneurial orientation has already implemented in small business (Haryati et al, 2018) (Haryati, Lilavalicakul, & Surrahman, 2019). Marketing orientation has significant influence to business performance (Ngai, Jimmy, & Ellis, 1998).…”
Section: Introductionmentioning
confidence: 99%